Child homicide or natural death? A case report of unexpected death of unusual asymptomatic acute laryngotracheobronchitis. (July 2016) - Zhuo, Luo; Liu, Liang; Ren, Liang; Liu, Qian
Cases involving the unexpected deaths of children are always a concern for the police and medical examiners alike. In particular, unexpected deaths due to asphyxia without obvious injuries sometimes make decisions regarding the manner of death more difficult. In the present case, a 2-year-old boy was found dead at home, and his mother was initially believed to have killed him. A complete autopsy and forensic investigation were performed, and no injuries were found on the body; however, marked laryngeal edema was observed. Histology showed extensive inflammatory infiltration of the mucosa and submucosa of the larynx, trachea, and bronchi. The cause of death was given as respiratory failure due to acute laryngotracheobronchitis; thus, the manner of death was natural. This case helps to remind the forensic community to keep an open mind and consider a broad differential diagnosis when approaching a case rather than jumping to a conclusion based solely on a preliminary investigation.